Short Communication: Genetic diversity and conservation strategy considerations for highly valuable medicinal tree of Taxus sumatrana in Indonesia - HENTI HENDALASTUTI RACHMAT; ATOK SUBIAKTO; KOICHI KAMIYA (Society for Indonesian Biodiversity, 2016)
Rachmat HH, Subiakto A, Kamiya K. 2016. Genetic diversity and conservation strategy considerations for highly valuable medicinal tree of Taxus sumatrana in Indonesia. Biodiversitas 17: 487-491. Genetic variation is considered to be the key factor for longterm survival of the species. The recognition of the existing genetic diversity is the preliminary phase in development of an effective strategy for conservation of forest tree species. Taxus sumatrana or is confined to grow naturally only in Asia, it is a rare and endangered species that in several Asian countries needs both ex situ and in situ protection program. In its natural distribution, T. sumatrana is the only Taxus species that reached its southernmost distribution to Sumatran forest-Indonesia and locally named as Sumatran Yew. The objective of this research was to determine the genetic variation of T. sumatrana as baseline information for designing conservation strategy of the species. Leaves samples were collected from two natural population of T. sumatrana in Mt. Kerinci (Sungai Penuh, Jambi) and Mt. Dempo (Pagaralam, South Sumatra), both sites are located along Bukit Barisan Mountain Ranges of Sumatra. We sequenced two non-coding chloroplast DNA (cpDNA) regions of trnL-trnF and psbC-trnS that each yielded 808 bp and 1092 bp, and rbcL gene of 523 bp, in which the total length covered 2423 bp. Surprisingly, we found no variation for all individuals and population, which means that the species is similar and both populations are not genetically structured. This study also revealed on how a proper conservation strategy should be practiced for the species as we know that without a sufficient amount of genetic variation, a population cannot evolve in response to changing environmental conditions. In situ conservation program is a must that can maintain the existence of the species while at the same time keeping the sustainability of the entire systems; in other side ex situ conservation strategy can take place as an additional effort to secure the genetic resources in case of the catastrophic events that might diminish their limited natural habitat.